Spatial planning as a tool for managing land resources in territorial communities - Butenko, Ye.; Vovna, M.; Prykhodko, M. (Land Management, Cadastre and Land Monitoring, 2024)
The article examines topical issues of spatial planning of land in territorial communities. The author analyzes the legal acts, namely: The Land Code of Ukraine, and a number of Laws of Ukraine, such as: "On Amendments to Certain Legislative Acts of Ukraine on Land Use Planning", "On Regulation of Urban Development", "On Land Management", and Resolutions of the Cabinet of Ministers of Ukraine, in particular: "Some Issues of Providing Subventions from the State Budget to Local Budgets for the Development of Comprehensive Plans for Spatial Development of Territories of Territorial Communities", "On Determining the Format of Electronic Documents of a Comprehensive Plan for Spatial Development of Territories of a Territorial Community, Master Plan of a Settlement, and Detailed Plan of a Territory". The reasons that provoked the process of delaying the full functioning of management structures in territorial communities and the development of comprehensive plans for spatial planning of the territory are analyzed. The data from the Prozoro web service in the context of "Urban Planning Services", the type of documentation is a comprehensive plan for the spatial development of territorial communities, are analyzed. The composition of project documentation for spatial planning of resource use in territorial communities is studied and its impact on the efficiency of community management is substantiated. The need for integrated planning in territorial communities is substantiated and the prospects for creating a database for integrated planning of the community territory are determined. It is determined that spatial planning is an effective tool for managing land resources in territorial communities of Ukraine. Key words: comprehensive plan of spatial development, land management documentation, urban planning documentation, land resources, spatial planning, management tool, territorial community, land resources management.